Multi-Material Implants for Temporomandibular Joint Disc Repair: Tailored Additive Manufacturing Production - Moura, Carla; Trindade, Daniela; Vieira, Milena; Francisco, Luís; Ângelo, David Faustino; Alves, Nuno (Frontiers in Bioengineering and Biotechnology, 2020)
Temporomandibular disorders (TMD) affect a substantial percentage of the population, and the resources spent on their treatment are considerable. Despite the worldwide efforts around Tissue Engineering of the temporomandibular joint (TMJ) disc, a proper implant offering a long-term solution for TMD was not yet developed. To contribute to these efforts, this work is focused on the research and development of implants for TMJ disc regeneration. Scaffolds and hydrogels mimicking the TMJ disc of black merino sheep were produced using different materials, poly(ε-caprolactone) (PCL) and poly(ethylene glycol) diacrylate (PEGDA), and as a multi-material structure. Different parameters of the scaffold manufacturing were assessed: the influence of processing temperatures, filament diameter, and biological environment. Moreover, two multi-material approaches were also assessed, scaffold with a hydrogel shell and scaffold with a hydrogel core. It was found that increasing temperature, the scaffolds’ porosity decreases, increasing their compressive modulus. Decreasing the filament size (300 to 200 μm) decreases the compressive modulus to almost half of the initial value. Scaffolds with 200 μm filaments are the ones with a closer modulus to the native disc and their properties are maintained under biological conditions. The introduction of a hydrogel core in these scaffolds was shown to be a promising solution for TMD.